Assessment of Quality of Life for Women with Multiple Sclerosis under 60 Years Old at AL-Najaf City - MSN, Sahar FakriJassim; Mohammed, Shatha SaadI (International Journal of Psychosocial Rehabilitation, 2020)
Background:MS is a progressive neurological condition that impacts the quality of life (QoL) of individuals at the physical, psychological and social aspect. It primarily impacts young adults with maximum potential, hinders the execution of their initiatives and causes doubt regarding their future Aims:The study conducted to assess of (QOL) of women with (MS) under 60 years of age and to correlated some factors with quality of life for MS women ,found out an association between demographic and clinical data with quality of life. Methods:Descriptive study has been conducted atAl-Najaf Al-Ashraf Health Directorate/ Al-Sadder Medical City/ Euphrates center for neuroscience period it’s from 24 September 2019 to 26 Jun 2020.the total participants were(N=75)women selecting by usingA non-probability sampling approach .the data collecting by usingestablished questionnaire and analyzed electronically by using SPSS program Results.largest proportion of (57.3%) of women were partially have problem in their physical health,(52%) of women were always have pain,(56%) of women were partially have problem in their emotional health, (49.3%) of women were never have problem in their social health,(48%) of women were sometime perform activities,(52%) of women were partially have cognitive function problem , (45.3%) of women were always have depression,(57.3%) of women were always have fatigue. Conclusions:.The study concludes that life quality of for women with multiple sclerosis under 60 years old is partially impaired in addition impairment appear in physical health, emotional health, social health, cognitive function, activities of daily living, pain, fatigue and depression appear the most factor affecting quality of life of MS women